Da Vassoura de Bruxa à Fazenda de Chocolate: a Reconversão Produtiva no Sul da Bahia - Carvalho, Joanna Isis Chaves (2020)
With the various crises it has gone through, especially after it started in the late 1980s, cocoa farming in southern Bahia has been presenting a scenario of productive conversion. The old cocoa monoculture, for a long time a source of wealth and responsible for subsidizing the high standard of living of the families producing the “golden fruit”, which was strongly affected by the entrance of the “witch's broom” fungus in the plantations, gave up its place highlighted in national and state economic indicators for the tertiary sector, highlighting the services sub-sector, in the Itabuna-Ilhéus micro-region. This article aims to analyze whether cocoa activity still has socioeconomic importance for southern Bahia, based on the alternatives found by producers for uplifting and renewing culture, which was called productive reinvention in the post-crisis period of 1989, confronting and questioning the very present tertiary sector in sustaining the regional economy. Methodologically, empirical data are analyzed regarding the processes of import/export and production/processing of cocoa, responsible for reflexes of cocoa in the economy and locoregional dynamics, which ratify the still significant importance of cocoa farming in the southern region of Bahia.